Surgical management of conventional grade I chondrosarcoma of long bones - Taninnit Leerapun (2018)
We retrospectively reviewed 70 patients with low-grade (Grade I) chondrosarcoma of the appendicular skeleton treated at the Mayo Clinic from 1980 to 2001. Fifty-four patients underwent wide resections and three patients underwent marginal excision for radiographically aggressive lesions. Thirteen patients were treated with intralesional curettage for more indolent lesions. The mean age of the patients was 43 years (range, 5-85 years) and the minimum followup was 0.2 year (mean, 8.5 years; range, 0.2-22.8 years). Of the patients who had wide resection, one experienced local recurrence and one had metastasis develop. One patient in the group treated with intralesional curettage had local recurrence and metastasis. We observed no difference in overall survival rate between the intralesional curettage group and the wide resection group. Although there was no difference in the treatment outcome between the two groups, patients with more radiographically aggressive lesions underwent more extensive surgery. The data suggest in selected patients less radiographically aggressive Grade I chondrosarcoma can be safely treated with intralesional curettage without compromising patient outcome. Level of Evidence: Level IV, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence. © 2007 Lippincott Williams & Wilkins, Inc.